Citizenship, generational status and mixed origin: An analysis of immigrant heterogeneity on academic performance in Portuguese state schools - Seabra, T.; Cândido, A. F. (Portuguese Journal of Social Science, 2022)
The official annual data on pupils of immigrant origin published by the Portuguese Directorate-General of Education and Science Statistics primarily focus on the citizenship of pupils, excluding those with Portuguese citizenship of immigrant origin or host country citizenship (descendants of immigrants). To address this limitation, this article employs microdata from Directorate-General of Education and Science Statistics of the Ministry of Education and Science (DGEEC/MEC), incorporating information on the pupils’ and parents’ countries of birth to identify descendants of immigrants. The study covers all pupils in Portugal enrolled in basic (primary and lower secondary) and secondary (upper secondary) education during the 2018–19 academic year in state schools of continental Portugal, aiming to explore the impact of different social categories on the academic performance gap among native, immigrant and pupils of immigrant origin. The analysis includes categories based on citizenship status and birthplace of pupils and parents, along with subcategories related to generational status and type of ancestry. The findings reveal previously unknown differences in academic performance among pupils with an immigrant background in Portugal, challenging traditional understandings. Notably, considering only the citizenship of the pupil underestimates the representation of pupils of immigrant origin, second-generation pupils often exhibit comparable or superior academic paths and pupils with parentage of mixed origin, especially those with a native parent, demonstrate a significant advantage in academic performance.